Chirality induction to achiral molecules by silica‐coated chiral molecular assemblies. Issue 9 (23rd July 2021) - Scalabre, Antoine; Okazaki, Yutaka; Kuppan, Balamurugan; Buffeteau, Thierry; Caroleo, Fabrizio; Magna, Gabriele; Monti, Donato; Paolesse, Roberto; Stefanelli, Manuela; Nlate, Sylvain; Pouget, Emilie; Ihara, Hirotaka; et al.
Abstract: Hybrid silica‐organic nanohelices are used to organize a large variety of nonchiral small organic molecules or inorganic anions to nanometer‐sized assemblies. Such chiral organization of achiral molecules induces chiroptical properties as detected by vibrational or electronic circular dichroism (CD), as well as from circularly polarized luminescence (CPL). Abstract : Hybrid silica‐organic nanohelices are used to organize a large variety of nonchiral small organic molecules or inorganic anions to nanometer‐sized chiral assemblies and to induce chiroptical properties as detected by vibrational or electronic circular dichroism (CD), as well as from circularly polarized luminescence (CPL).